2019
DOI: 10.1038/s41598-019-45684-0
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive, multiscale framework for evaluation of arrhythmias arising from cell therapy in the whole post-myocardial infarcted heart

Abstract: Direct remuscularization approaches to cell-based heart repair seek to restore ventricular contractility following myocardial infarction (MI) by introducing new cardiomyocytes (CMs) to replace lost or injured ones. However, despite promising improvements in cardiac function, high incidences of ventricular arrhythmias have been observed in animal models of MI injected with pluripotent stem cell-derived cardiomyocytes (PSC-CMs). The mechanisms of arrhythmogenesis remain unclear. Here, we present a comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 107 publications
1
18
0
Order By: Relevance
“…Studies in large animals have demonstrated long-term efficacy but also defined a significant safety signal of generally transient but potentially fatal arrhythmias. As demonstrated in earlier studies ( Liu et al., 2018 ; Romagnuolo et al., 2019 ; Shiba et al., 2016 ), EA is a predictable complication of cardiac remuscularization therapy for MI ( Yu et al., 2019 ). In the NHPs, EA typically presents as a wide complex tachycardia with a variable electrical axis ( Chong et al., 2014 ; Liu et al., 2018 ), and this was reproduced in the minipig recently by the Laflamme laboratory ( Romagnuolo et al., 2019 ).…”
Section: Discussionsupporting
confidence: 54%
“…Studies in large animals have demonstrated long-term efficacy but also defined a significant safety signal of generally transient but potentially fatal arrhythmias. As demonstrated in earlier studies ( Liu et al., 2018 ; Romagnuolo et al., 2019 ; Shiba et al., 2016 ), EA is a predictable complication of cardiac remuscularization therapy for MI ( Yu et al., 2019 ). In the NHPs, EA typically presents as a wide complex tachycardia with a variable electrical axis ( Chong et al., 2014 ; Liu et al., 2018 ), and this was reproduced in the minipig recently by the Laflamme laboratory ( Romagnuolo et al., 2019 ).…”
Section: Discussionsupporting
confidence: 54%
“…Studies in large animals have demonstrated long-term efficacy but also defined a significant safety signal of generally transient but potentially fatal arrhythmias. As demonstrated in earlier studies (12)(13)(14), EA is a predictable complication of cardiac remuscularization therapy for myocardial infarction (22). In the NHP, EA typically presents as a wide-complex tachycardia with a variable electrical axis (11,12), and this was reproduced in the minipig recently by Laflamme laboratory (14).…”
Section: Discussionmentioning
confidence: 72%
“…1 ) [ 159 ]. Indeed, multiscale 3D whole-heart modeling has recently been developed to determine how varying parameters of cell delivery and transdifferentiation could result in focal ectopy, heart block, and reentry [ 20 ••].…”
Section: Mathematical Models For Addressing the Mechanisms Of Arrhythmogenesismentioning
confidence: 99%
“…The hiPSC-derived cardiomyocytes (hiPSC-CMs) can be obtained from healthy or diseased individuals, and provide the inexhaustible source for human disease modeling. Finally, recent development in multiscale computational studies provides yet another powerful tool to quantitatively test the mechanisms of cardiac arrhythmias in cardiac repair [ 20 ••].…”
Section: Introductionmentioning
confidence: 99%